Lactic Acid Bacteria: Genetics, Metabolism and Applications 1999
DOI: 10.1007/978-94-017-2027-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage defence systems in lactic acid bacteria

Abstract: The study of the interactions between lactic acid bacteria and their bacteriophages has been a vibrant and rewarding research activity for a considerable number of years. In the more recent past, the application of molecular genetics for the analysis of phage-host relationships has contributed enormously to the unravelling of specific events which dictate insensitivity to bacteriophage infection and has revealed that while they are complex and intricate in nature, they are also extremely effective. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
135
1
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(142 citation statements)
references
References 111 publications
1
135
1
5
Order By: Relevance
“…These measures can be divided into four groups: (i) inhibition of phage adsorption, (ii) blockage of phage DNA injection, (iii) abortive infection mechanisms, and (iv) restriction of phage DNA (Forde & Fitzgerald, 1999;Coffey & Ross, 2002). These defence mechanisms are often located on plasmids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These measures can be divided into four groups: (i) inhibition of phage adsorption, (ii) blockage of phage DNA injection, (iii) abortive infection mechanisms, and (iv) restriction of phage DNA (Forde & Fitzgerald, 1999;Coffey & Ross, 2002). These defence mechanisms are often located on plasmids.…”
Section: Introductionmentioning
confidence: 99%
“…Their enemies are not people who hate buttermilk, but virulent phages whose existence relies on propagation within bacterial cells. To combat phages, LAB have developed multiple molecular strategies.These measures can be divided into four groups: (i) inhibition of phage adsorption, (ii) blockage of phage DNA injection, (iii) abortive infection mechanisms, and (iv) restriction of phage DNA (Forde & Fitzgerald, 1999;Coffey & Ross, 2002). These defence mechanisms are often located on plasmids.…”
mentioning
confidence: 99%
“…These include surface alterations to avoid phage adsorption, prevention of phage DNA injection, restriction of incoming DNA, acquiring phage-specific immunity through clustered regularly interspaced short palindromic repeats (7) and abortive infection (Abi). Abi systems provide population protection by promoting ''altruistic suicide'' of an infected bacterium (8). The majority of Abis have been found on plasmids of Gram-positive lactococcal strains (9), but some have been found in Gram-negative species, including Escherichia coli, Vibrio cholerae, and Shigella dysenteriae (10)(11)(12).…”
mentioning
confidence: 99%
“…Triplicate results indicated that > 99% of /c2 adsorbed to the transconjugant DPC5101 thus eliminating the possibility of an adsorption inhibition (Ads) system for this phage being present on the plasmid. Given the observed reduction in plaque size for phage c2 and the total resistance against phage 712, the pCBG104 resistance system has similarities to many lactococcal abortive infection mechanisms previously reported (for review see Forde and Fitzgerald 1999). Analysis of intracellular phage c2 and phage 712 DNA replication revealed that the increase in phage DNA content of cells following infection was delayed in the presence of pCBG104.…”
Section: Identification Of Bacteriocin-linked Bacteriophage Resistancmentioning
confidence: 66%
“…Nevertheless, bacteriophage sensitivity can be remedied by targeted strain improvement, which focuses on the introduction of plasmids harbouring specific phage resistance genes (Klaenhammer and Fitzgerald 1994;Forde and Fitzgerald 1999). Such approaches to strain improvement require that the plasmid contains a suitable marker for selection of transconjugants.…”
Section: Introductionmentioning
confidence: 99%